The Role of Teachers in Fostering the Entrepreneurial Attitude of Elementary School Students through Scouting - Wahyuni Baturetno; Ahmad Fathoni; Minsih Zifa; Yenny Prastiwi (Jurnal Prima Edukasia, 2023)
Entrepreneurial education needs to be instilled in children from an early age so that they are ready to face the challenges of the times. This research aims to describe: 1) the role of teachers in fostering entrepreneurial attitudes through scouting. 2) obstacles and solutions in fostering entrepreneurial attitudes through scouting This research uses qualitative methods with a phenomenological approach. This research was conducted at one of the State Elementary Schools in Baturetno Wonogiri Regency, Central Java. The data collected is qualitative data in the form of narratives about the role of teachers in fostering entrepreneurial attitudes through scouting. The data source used is the primary data source and the secondary data source. Data collection techniques in this study include observation techniques, interviews and documentation. Data analysis techniques in this study use interactive techniques. The results of research 1) In carrying out scouting activities or scout excursions are carried out on Fridays when at the time of lessons, because learning is still face-to-face limited.2) The role of teachers in fostering student entrepreneurship attitudes by building entrepreneurship attitudes, so that learners like challenges, creative and innovative, and more courageous in making decisions. 3) In cultivating an entrepreneurial attitude there are several obstacles that must be faced by scouting teachers. There are obstacles that come from teachers and students The existing constraints must be overcome so that the desired goal can be achieved